2018
DOI: 10.1111/hepr.13062
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a scoring system to predict progression to acute‐on‐chronic liver failure in patients with acute exacerbation of chronic hepatitis B

Abstract: Aim The aim of this study was to develop and validate a scoring system to predict the progression to acute‐on‐chronic liver failure (ACLF) in patients with acute exacerbation (AE) of chronic hepatitis B (CHB). Methods The baseline characteristics of 474 patients with AE of CHB were retrospectively reviewed; 280 and 194 patients were randomly assigned to the derivation and validation cohorts, respectively. Univariate risk factors associated with ACLF development were entered into a multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
2
14
1
Order By: Relevance
“…Several risk factors for post-admission development of ACLF in patients with SAE were different from those in patients with AE. In our previous study, LC was not an independent factor associated with the development of ACLF in patients with AE[19]. In this study, however, LC was an independent risk factor for post-admission progression of both HD and ACLF in patients with SAE.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Several risk factors for post-admission development of ACLF in patients with SAE were different from those in patients with AE. In our previous study, LC was not an independent factor associated with the development of ACLF in patients with AE[19]. In this study, however, LC was an independent risk factor for post-admission progression of both HD and ACLF in patients with SAE.…”
Section: Discussioncontrasting
confidence: 69%
“…Forty-three (26.2%) patients had progression to HD and 29 (17.7%) patients had progression to ACLF within 28 d of admission. Therefore, the patients in this study had more serious liver injury than patients with AE as previously reported (only 7.59% of patients had progression to ACLF)[19]. We found that LC was an independent risk factor associated with progression to both HD and ACLF, while high MELD score, high AST, and low PTA were independent risk factors associated with progression to ACLF.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…ACLF is a static diagnosis for liver function status, which is diagnosed until the appearance of acute deterioration of liver function with the progression of disease. 21 With the dynamic development of disease, severe CHB patients may not develop liver failure and instead experience a gradually restoration of function, but the status may also may further aggravate to liver failure and lead to diagnosis of ACLF. Thus, in the early phase of acute exacerbation of CHB, prediction of the risk of the occurrence of ACLF, timely prevention, intervention and standardized treatment to prevent its progression to ACLF will no doubt improve the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%